Um olhar historiográfico da BNCC no período de 2015 a 2018: que álgebra é proposta? - Adriano Da Fonseca Melo (2024)
This thesis deals with the Base Nacional Comum Curricular (BNCC) formation movement, as well as the knowledge selections to be candidate to establish the knowledge to be developed with basic education students on algebra thematic axis. This research has a qualitative and historical approach, in which we used documentary research to collect information, thus seeking to analyze possible transformations of knowledge in algebra teaching during the process of establishing the Base Nacional Comum Curricular for the basic education, based on the writers and critical readers view in the preparation of this document. To direct the investigative work, we seek to answer the question: how can the transformations of knowledge in the algebra teaching in basic education be interpreted, from the elaboration to the implementation of the Base Nacional Comum Curricular, taking into account the opinions of the editors and the notes from de the ‘critical readers’ of the document? In this regard, we resorted to researchers who seek to establish basis for a historical view based on the Present Time History, in which the past, present and future present a tenuous border, since the historian’s view is directed to the events that are happening and there is no way to define the action results. The agents of the actions seek input from their space of experiences and their expectations for the future, establishing a horizon of expectation, although the act can be mobilized by conflicts caused by the impacts of generations as well as by social demands. In this case, BNCC first emerges as a social demand represented by official documents, such as the Law of Directive and Basis for Education, the National Curricular Guidelines for Basic Education and the National Education Plan, starting from the premise that these documents elaboration had the society segments participation. Moreover, BNCC in its constitution process had moments of public consultation in which the society had the opportunity to participate, however the analysis might infer that the BNCC text present ideas that tend to one side of the society and do not consider all of its contributions. Among the segments that had ideas that were considered are institutions linked to business groups and other international institutions invited to monitor the entire process. In regard to the mathematical knowledge, it is noted that through the introductory texts of the area, the specific skills, the objectives in the first and second version and the skills in the final version that there were changes in the selection and the graduation of the algebraic content, signaling that in each version a proposed teaching program can be identified. We characterize these changes as graduation conversions, since from one version to another, the writers resume the selection and graduation process to rewrite both the introductory text and the distribution of knowledge in the algebraic field within the school years. Finally, the final version presents objects of knowledge for the algebra thematic axis that ranges from algebra as generalized arithmetic passing through algebra as the study of procedures for solving problems, the relationship between quantities and structure. In this regard, the editors indicate that it is important for the student to understand the different uses of the letter as unknown, variable and indeterminate number. Keywords: Base Nacional Comum Curricular; Knowing how to teach; Knowledge to teach; History of the present time; Algebra